Health Risk and Environmental Assessment of Cement Production in Nigeria - Mmemek-Abasi Etim; Kunle Babaremu; Justin Lazarus; David Omole (Atmosphere, 2021)
The cement manufacturing industry has played a fundamental role in global economic development, but its production is a major facilitator to anthropogenic CO2 release and solid waste generation. Nigeria has the largest cement industry in West Africa, with an aggregate capacity of 58.9 million metric tonnes (MMT) per year. The Ministry for Mines and Steel Development asserts that the nation possesses total limestone deposits of around 2.3 trillion MT with 568 MMT standing as established reserves and 11 MMT used. Cement industries are largely responsible for releasing air pollutants and effluents into water bodies with apparent water quality deterioration over the years. Air pollution from lime and cement-producing plants is seen as a severe instigator of occupational health hazards and work-related life threats, negatively affecting crop yields, buildings, and persons residing in the vicinity of these industries. World Bank observed in 2015 that 94% of the Nigerian populace is susceptible to air pollutants that surpass WHO guidelines. In 2017, World Bank further reported that 49,100 premature deaths emanated from atmospheric PM2.5, with children beneath age 5 having the greatest vulnerability owing to lower respiratory infections, thereby representing approximately 60% of overall PM2.5-induced deaths. Cement manufacturing involves the significant production of SO2, NOx, and CO connected to adverse health effects on humans. Sensitive populations such as infants, the aged, and persons having underlying respiratory ailments like asthmatics, emphysema, or bronchitis are seen to be most affected. Consequently, in addressing this challenge, growing interests in enacting carbon capture, usage, and storage in the cement industry is expected to alleviate the negative environmental impact of cement production. Still, no carbon capture technology is yet to achieve commercialization in the cement industry. Nonetheless, huge advancement has been made in recent years with the advent of vital research in sorption-enhanced water gas shift, underground gasification combined cycle, ammonium hydroxide solution, and the microbial-induced synthesis of calcite for CO2 capture and storage, all considered sustainable and feasible in cement production.